Flexible alpha camera for detecting plutonium contamination. (August 2017) - Morishita, Yuki; Yamamoto, Seiichi; Izaki, Kenji; Kaneko, Junichi H.; Nemoto, Norio
Abstract: We developed a new imaging detector called flexible alpha camera that can identify Pu contamination in narrow spaces at work sites. The thickness of the flexible alpha camera is only ∼1/5th that of the ZnS(Ag) scintillation detector which is commonly used for detecting Pu contamination, and its efficiency in the 4-pi direction is 42.7% for 5.5-MeV alpha particles. The minimal detectable activity (MDA) is 0.014 Bq measured in 30 min. Four types of PuO2 samples, taken from a duct, bag-in/bag-out port, glovebox glove, and vinyl sheet, were measured by the flexible alpha camera. In a two-dimensional distribution of alpha particles, PuO2 was identified automatically using the "AnalyzeParticle" function in the ImageJ plugin, and its activity was evaluated. When acquisition time increased from 10 min to 30 min, a Pu spot with low activity was identified. To verify the measurement in narrow space, a fume hood to which a PuO2 particle was attached was measured using the flexible alpha camera. Since the flexible alpha camera has the thin-thickness of 12 mm and can obtain two-dimensional distribution and energy spectrum of alpha particles, it is effective for detecting Pu contamination in narrow spaces of equipment. Highlights: A new imaging detector called flexible alpha camera was successfully developed. The thickness of the flexible alpha camera is only ∼1/5th that of the ZnS(Ag) scintillation detector. Locations of PuO2 samples were identified by the flexible alpha camera. The activity of Pu measured by the flexible alpha camera corresponded with that measured by the ZnS(Ag) alpha counter.